Study of acute toxicity of GIZh-298 - A. V. Sorokina; S. V. Alekseeva; I. A. Miroshkina; A. V. Volkova; K. S. Kachalov; A. D. Zakharov; I. V. Alekseev; A. D. Durnev (LLC "Publisher OKI", 2023)
Relevance. Assay of acute toxicity is a mandatory step in a preclinical safety study of medicines and pharmaceutical substances. The purpose of this study was to determine the parameters of acute toxicity of the substance GIZH-298. Methods. GIZH-298 was administered once orally to outbred mice of both sexes at doses of 350-550 mg/kg. Control mice received 0.5 ml of 1 % starch solution under the same conditions. During the experiment, the death of animals, signs of intoxication were observed, and the clinical picture was recorded. Pathological anatomical autopsy of the dead mice was performed as they died. Surviving mice were autopsied 14 days after the start of the experiment, immediately after their euthanasia. Results. The average lethal doses of the GIZh-298 substance when administered orally to mice were determined: LD50 in females was 356 mg/kg, LD50 in males was 438 mg/kg. Conclusion. Compound GIZH-298 for oral administration according to the classification of Sidorov K.K. (1973) is a moderately toxic substance and can be assigned to the 3rd class of toxicity, and in accordance with GOST 12.1.007-76 - to the 3rd hazard class.